Toolkit for Service Learning. Building Community Relationships and Partnerships - Rachel, Whalen; Amy, Kuo Somchanhmavong; Shorna, Allred; Tariq, Zaman (UNIMAS Publisher, 2022)
I first met Amy Kuo Somchanhmavong and Shorna Allred at the International Conference on Engaged Learning and Information and Communication Technologies (ICTs) for Development in the University Curriculum. It was co-organized by Cornell University, the University of Selangor and the Asian Institute for Development Communication, and held in Selangor, Malaysia from 3_5 June 2014. Amy and Shorna presented their service learning experiences working with rural communities in Asia while I outlined my experiences with UNIMAS from introducing ICTs to remote communities in Malaysian Borneo. We clicked immediately. After boldly suggesting to Amy and Shorna to consider linking their programme to ours, they displayed admirable courage and creativity to take the idea seriously, with the result that, after a great deal of meticulous planning, preparation and logistical co-ordination, the first cohort of Cornell- UNIMAS service learning students, which included Rachel Whalen, arrived in the remote and isolated community of Long Lamai on Borneo in January 2016. I had the good fortune to be invited to join them on that groundbreaking initiative, which has since blossomed into many more such student community encounters and a fully-fledged campus-wide service learning programme at UNIMAS. In addition to Amy and Shorna’s professionalism and dedication, what struck me most was how well the students adapted to the totally alien environment of Borneo’s interior, and, equally critical, how well the community warmed to their presence. Without doubt, these outcomes were in no small part due to the assiduous development and implementation of the processes outlined in this book. My experiences have taught me that cross-cultural community development encounters are laden with pitfalls for the unprepared. Had I had access to the accumulated wisdom and advice here, my own efforts would have been greatly eased. Anyone engaged in service learning needs practical advice from people with direct experience who are drawn from the entire range of relevant stakeholders. The service learning programme that is featured here has spawned a broad catalogue of highly desirable outcomes. The participating students from Cornell are engaged within the University’s Global Citizenship and Sustainability Program which fosters cross-cultural learning while building skills in community-based research. The feedback I have received from them suggests it does far more than this; engendering a life-changing outlook on the world that they will carry forward as tomorrow’s leaders into whatever occupation they adopt. The communities benefit from their joint participation through the injection of external perspectives on localised development schemes that strengthen resilience and promote sustainable livelihoods. UNIMAS has absorbed its learning from the engagement with Cornell and has now integrated service learning into every academic programme that it offers. Finally, arising from its origin within another programme for deploying ICTs among rural communities, thereby adding social and economic value to the technology, the approach to Service learning that is described here, involving local managers of community internet centres, achieves the additional benefit of helping to achieve the full potential of digital technology for citizens who have the least access to it. Service learning allows students to engage with communities in order to apply the knowledge and skills that they have learned in the classroom to their needs. This service learning Toolkit will show you how to do this. Roger Harris